Carpometacarpal Osteoarthritis Pain of the Thumb Can Be Relieved by Commercial Beverage Carbonated Water - Masaaki Nakajima (Case Reports in Anesthesiology, 2024)
Thumb carpometacarpal (CMC) arthropathy pain is treated using carbonated water—a commercially available beverage. The right hand (affected side) was bathed once daily in carbonated beverage water (37°C) for 20 min. Prior to treatment, the visual analogue scale score of pain was 73 mm; 1 week after the treatment, it was 0 mm. Commercial carbonated water immersion was effective for thumb CMC arthropathy pain. Commercial carbonated water is inexpensive and easy to obtain, making it suitable for home carbonation therapy.